2020
DOI: 10.1049/trit.2019.0083
|View full text |Cite
|
Sign up to set email alerts
|

Cylindrical neutrosophic single‐valued number and its application in networking problem, multi‐criterion group decision‐making problem and graph theory

Abstract: In this study, the authors envisage the neutrosophic number from various distinct rational perspectives and viewpoints to give it a look of a conundrum. They focused and analysed neutrosophic fuzzy numbers when indeterminacy and falsity functions are dependent on each other, which serves an indispensable role for the uncertainty concept. Additionally, the idea of cylindrical neutrosophic single-valued number is focused here, when the indeterminacy and falsity functions are dependent to each other using an infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4
1

Relationship

3
7

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 56 publications
0
15
0
1
Order By: Relevance
“…Another study suggested arithmetic and geometric operations under pentagonal neutrosophic numbers along with the application based on MCGDM in mobile communication [9]. The neutrosophic numbers are gaining much interest of the researchers as time passes, for instance, an MCGDM scheme was proposed under the cylindrical neutrosophic domain [10].…”
Section: Introductionmentioning
confidence: 99%
“…Another study suggested arithmetic and geometric operations under pentagonal neutrosophic numbers along with the application based on MCGDM in mobile communication [9]. The neutrosophic numbers are gaining much interest of the researchers as time passes, for instance, an MCGDM scheme was proposed under the cylindrical neutrosophic domain [10].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, researchers have introduced pentagonal [4], hexagonal [5], heptagonal [6] fuzzy numbers and its application in different fields. Wang et al manifested the conception of single-valued neutrosophic set (SVNS) [7] and interval neutrosophic set (INS) [8] which are subclasses of NSs and many other recent works [9][10][11][12] have improved and bring innovation into the NS hypothesis. Liu and Yuan [13] proposed the idea of triangular intuitionistic fuzzy set (TIFN) which is a combination of triangular fuzzy number and intuitionistic fuzzy number.…”
Section: Introductionmentioning
confidence: 99%
“…23–26 Neutrosophic number was further extended to cylindrical neutrosophic number and used in solving networking and minimal spanning tree problems. 27 The concept of fuzzy polygroups was generalised further to single-valued neutrosophic polygroups and its sets. 28 For better modelling of real-life applications, the crisp, fuzzy, intuitionistic fuzzy and neutrosophic sets were further generalised into plithogenic sets.…”
Section: Introductionmentioning
confidence: 99%